Optimasi Kombinasi Ramuan Etnomedisin Penumbuh Rambut Nusa Tenggara Timur Menggunakan Orthogonal Stimulus Response Method Pada Kepadatan Rambut Mencit (Mus musculus) - Taek, Maximus M.; Megawati, Dewi Sinta; Subiyakto, Erlangga Sufi; Khoirunnisa, Zahra; Maulina, Novia; Muslikh, Faisal Akhmal; Ma’arif, Burhan (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to optimize a traditional ethnomedicinal formulation from East Nusa Tenggara (RENTT) as a natural hair-growth candidate and to evaluate its antioxidant activity and biological effectiveness using an alopecia model. A true experimental design was applied using the Taguchi–Orthogonal Stimulus Response Method (OSRM) to determine the optimal combination of five plant extracts, namely Aleurites moluccanus, Hibiscus rosa-sinensis, Ficus benjamina, Polyscias scutellaria, and Hibiscus tiliaceus. In vitro optimization was conducted using the DPPH radical scavenging assay with a Taguchi L27 orthogonal array design. The optimal formulation was subsequently evaluated in vivo using male mice (Mus musculus) with croton oil–induced alopecia. Hair growth effectiveness was assessed based on hair density percentage through histomorphometric analysis with hematoxylin–eosin staining. The results demonstrated that the optimal RENTT formulation exhibited very strong antioxidant activity with an IC₅₀ value of 27.46 ppm. Taguchi analysis identified F. benjamina as the most influential factor in determining formulation performance. In vivo evaluation showed that the RENTT-treated group achieved the highest hair density (49.45 ± 4.70), which was significantly higher than that of the positive control, negative control, and normal control groups. In conclusion, the optimized RENTT formulation demonstrates strong antioxidant properties and a significant stimulatory effect on hair growth, indicating its promising potential as a natural cosmeceutical product based on the local wisdom of East Nusa Tenggara.